Pengaruh Model Pembelajaran Means Ends Analysis Terhadap Keaktifan Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Simanindo Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2024)
The aim of this research is to determine the positive and significant influence of the Means Ends Analysis learning model on the active learning of Christian Religious Education and Characteristics of class XI students at SMA Negeri 1 Simanindo for the 2023/2024 academic year. The research method used is a quantitative method with inferential statistics. The population is all class Data was collected using a positive closed questionnaire with 40 items, namely 24 items for variable Negeri 1 Simanindo for the 2023/2024 academic year, proven through the following data analysis: 1) Test analysis requirements: a) positive relationship test obtained by the value rxy = 0.712 > rtable(a=0.05,n=46) = 0.291. b) Testing a significant relationship obtained tcount= 6.726> ttable(a=0.05, dk=n-2=44)= 2.021. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=20.23+0.37X. b) Regression coefficient of determination test (r2) = 50.7%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=31, dk denominator=n-2=46-2=44) namely 45.264 > 1.51. Thus Ha is accepted and H0 is rejected.